MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF AL-QUR'AN - Zainuddin; Tutik Hamidah (UNZAH Genggong, 2022)
This study aims to determine educational management from the perspective of the Qur'an. This research uses qualitative methods with a literature study approach. The result of this research is that management is the process of utilizing all resources through people and working with them. The process is to achieve common goals effectively, efficiently, and productively. The principles of educational management according to the Qur'an include sincerity, honesty, trustworthiness, justice, responsibility, dynamic, practical, flexible, selective, effective and efficient, open, cooperative and participatory, giving warnings, giving directions and directions. The conclusion of this study is henceforth, management functions such as planning, organizing, mobilizing, and supervising. This function is a process that must be carried out by all parties involved in an organization. These functions will determine whether or not management performance is successfulKeywords: Management, Qur’an